2021
DOI: 10.1007/s00418-020-01955-w
|View full text |Cite|
|
Sign up to set email alerts
|

Lung organoids: advances in generation and 3D-visualization

Abstract: The lung is comprised of more than 40 distinct cell types that support a complex 3-dimensional (3D) architecture that is required for efficient lung function. Loss of this proper architecture can accommodate and promote lung disease, highlighting researchers’ growing need to analyze lung structures in detail. Additionally, in vivo cellular and molecular response to chemical and physical signals, along with the recapitulation of gene-expression patterns, can be lost during the transition from complex 3D tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Thus, these results extend and confirm the hypothesis that a hormone-effected decrease in epithelial cell polarity is required for the receptivity of the endometrium for embryo implantation. Moreover, the authors demonstrate the great value and utility of using cellular spheroids for 3D tissue models in human reproductive research, as has also been shown recently for other tissues such as lung (Cunniff et al 2021) and diseases such as cancer (Huch and Koo 2015).…”
Section: Implanting the Idea Of Steroid Hormone Influence On Epithelial Cell Polaritysupporting
confidence: 52%
“…Thus, these results extend and confirm the hypothesis that a hormone-effected decrease in epithelial cell polarity is required for the receptivity of the endometrium for embryo implantation. Moreover, the authors demonstrate the great value and utility of using cellular spheroids for 3D tissue models in human reproductive research, as has also been shown recently for other tissues such as lung (Cunniff et al 2021) and diseases such as cancer (Huch and Koo 2015).…”
Section: Implanting the Idea Of Steroid Hormone Influence On Epithelial Cell Polaritysupporting
confidence: 52%
“…The label-free imaging capability of ODT can demonstrate synergetic effects in combination with the use of non-toxic tunable RI media for imaging large biological samples over a long time. Iodixanol has been proven to be biocompatible in cell imaging [21], and the label-free nature of ODT enables long-term monitoring of cells that are implanted into humans [55][56][57]. Given the simple and biocompatible nature of the proposed method, it could potentially be used for the study of developmental biology or regenerative medicine [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The human lung is home to over 40 individual cell types that coordinate to maintain respiratory function [ 83 , 84 ]. Accordingly, communication between these participating cells is often at the heart of major events such as lung organogenesis and pathogenesis.…”
Section: Pulmonary Organoids: Organized Cell–cell Interactionsmentioning
confidence: 99%